Piloting Macroinsurance for Microenterprises in Post-Revolution Egypt - Groh, Matthew; McKenzie, David (World Bank, Washington, DC, 2014)
This note discusses the results of a pilot of an innovative insurance product, which aims to protect small firms from macroeconomic and political risk that might inhibit them from investing.